THE INFLUENCE OF NORDIC WALKING IN THE FOREST ON THE EMOTIONAL STATE OF STUDENTS OF ALTAI STATE MEDICAL UNIVERSITY - Bardakova , A. Y.; Surcova, A. D.; Lobygina , N. М. (Modern Psychology, 2019)
In this article, we examined the relationship between Nordic walking on "fresh air" and change the emotional background of students, as well as the causes that might trigger these changes. It was suggested that effective practical application of the information received.
Keywords: Luscher, Nordic walking, students, test, emotional state, stress, forest.